Urban population and economic growth: South Asia perspective - Sandip Sarker; Arifuzzaman Khan; Mehdad Mamur Mannan (European Journal of Government and Economics (EJGE), 2016)
Previously economic growth was generally discussed in terms of foreign direct investment (FDI), educational growth, savings, investments, inflation as well as trade openness of a nation. Very recently it has been identified that population is one of the major determinants of economic growth of a nation. In the recent years, the study of urbanization has gained a matter of concern in developing countries as it has been recognized as part of a larger process of economic development which is affecting developing countries. South Asian countries are one of the emerging economics and growing at a faster rate over the past few years. At the same time, population of South Asia is growing at a significant rate. Therefore the study has attempted to identify the causal relationship between urban population and economic growth in South Asia using a panel data analysis. The study makes use of the Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP), Pesaran as well as Fisher methods for panel unit root test. The panel Pedroni cointegration test suggests that there is long run relationship between the variables. The further panel Vector Error Correction Model (VECM) suggests that there is long run causality running from urban population growth to economic growth in South Asia. The study concludes that the growth of urban population can have significant impact on economic growth in South Asia in the long run.
Keywords: 330; Urban Population; Economic Growth; South Asia; Vector Error Correction Model; Panel Data.